Metaphors and education: comparison of metaphors for education among parents of children in school and home education. (3rd July 2018) - Neuman, Ari; Guterman, Oz
Abstract: Home education is a practice in which parents choose not to send their children to school or public educational frameworks, and to teach them at home instead. This is not new, but in several Western countries the numbers of families home educating has been growing recently. The research on home education has used quantitative and qualitative instruments. One of the qualitative methods employed to learn about the worldviews of research participants is metaphor analysis, in which the interviewees are asked to suggest metaphors for the research subject. However, there is a lack of research on home education using metaphor analysis. The present research compared the metaphors of 15 home educating mothers with those of 15 mothers who sent their children to school. The research findings indicate differences between the groups in the degree to which the metaphors were positive, and different perceptions regarding the nature and functions of education itself.